Changes of structure and functional properties of rice protein in the fresh edible rice during the seed development - Dan Li; Mingjing Yao; Yang Yang; Bing Wang; Dongjie Zhang; Na Zhang (Food Science and Human Wellness)
It has been reported that fresh edible rice has more bioactive compounds and its protein is easier to digest and has lower hypoallergenic than mature rice. In this paper, the changes in structure and functional properties of proteins at five different stages, including early milky stage (EMS), middle milky stage (MMS), late milky stage (LMS), waxy ripe stage (WS) and ripening stage (RS), during the seed development were investigated. It was found that with the seed developing, the molecular weight of fresh rice protein gradually become larger while the secondary structure changed from the highest content of disordered structure at MMS to the highest content of ordered structure at RS, which affect the surface hydrophobicity and then the functional properties of proteins, including foaming properties, emulsifying properties and oil holding capacity. Fresh rice protein at MMS has the strongest surface hydrophobicity while fresh edible rice protein at RS has the strongest oil holding capability. The results of our study can provide a theoretical basis for the application of fresh rice protein in the food industry and help to develop new fresh edible rice food.